1999
DOI: 10.1177/0013164499591010
|View full text |Cite
|
Sign up to set email alerts
|

A Confirmatory Factor Analysis of the Competing Values Instrument

Abstract: The competing values framework (CVF) formulated by Quinn and his colleagues was developed to specify the criteria of organizational effectiveness and was later used to study a wide range of organizational phenomena such as culture and change. We extend this work by using structural equations modeling (LISREL) to (a) test the CVF and (b) refine a scale that identifies the extent to which managers and other organizational constituencies use the framework’s criteria to evaluate organizational effectiveness. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 20 publications
8
64
0
6
Order By: Relevance
“…Comparison of the current organizational profile with the ideal can identify imbalances and generate discussion concerning strategies for improvement and growth in each of the cultural types (Cameron & Quinn, 1999). Survey feedback can also be transformed into an action research process based on the members clarifying what the desired culture means, the benefits, and the proposed changes to ensure the development of the desired culture (Kalliath, Bluedorn, & Gillespie, 1999). According to Quinn and Cameron (1983), emphasizing only the values in a single quadrant could be dysfunctional.…”
Section: The Competing Values Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the current organizational profile with the ideal can identify imbalances and generate discussion concerning strategies for improvement and growth in each of the cultural types (Cameron & Quinn, 1999). Survey feedback can also be transformed into an action research process based on the members clarifying what the desired culture means, the benefits, and the proposed changes to ensure the development of the desired culture (Kalliath, Bluedorn, & Gillespie, 1999). According to Quinn and Cameron (1983), emphasizing only the values in a single quadrant could be dysfunctional.…”
Section: The Competing Values Frameworkmentioning
confidence: 99%
“…Yeung, Brockbank, and Ulrich (1991) studied over 10,000 business executives and found a Cronbach's alpha coefficient close to .80. Kalliath, Bluedorn, and Gillespie (1999) used structural equation modeling to test the factor structure of the OCAI (Quinn & Spreitzer, 1991) and reported "excellent validity and reliability estimates" (p. 143). Colyer (2000) also reported moderate to high internal consistencies of the subscales as indicated by Cronbach's alphas that ranged from .58 to .88.…”
Section: The Competing Values Frameworkmentioning
confidence: 99%
“…As criticism, Hartnell, Ou, and Kinicki (2011) found varying relationships between three culture types and efficiency, together with how different strategies fit with certain culture types to attain competitive advantage. However, a factor analysis of 300 hospital managers has given convincing evidence of the CVF's reliability and validity (Kalliath et al, 1999). And it has been used in a variety of settings, including studies of organizational culture in European companies (Van Muijen, 1999) and managerial perceptions among Australian managers (Lamond, 2001).…”
Section: Effects Of Business Model Development Projects On Organizatimentioning
confidence: 99%
“…Several authors have found consistent evidence for the validity of the CVM (Quinn and Spreitzer 1991;Zammuto and Krakower 1991;Denison and Mishra 1995;Howard 1998;Cameron and Quinn 1999;Kalliath et al 1999;Lamond 2003;Kwam and Walker 2004;Ralston et al 2006;Rhee and Moon 2009). To measure the four culture quadrants in a sample of 796 executives, Quinn and Spreitzer (1991) used an ipsative questionnaire, which is a forerunner of the OCAI (Cameron 1978), and contrasted it with a normative counterpart, based on Likert-type scales (Quinn, undated, not published).…”
Section: Application Domain: Organizational Culture and Valuesmentioning
confidence: 99%
“…The CVM model and associated OCAI instrument have been widely used for assessing and profiling organizational cultures in a variety of organizations (Quinn and Cameron 1983;Cameron and Quinn 1999, 2006, 2011Cameron 2004): for instance, health care (Kalliath et al 1999); veterans health administration (Helfrich et al 2007); construction firms (OneyYazic et al 2006); libraries (Kaarst-Brown et al 2004;Stanton 2004;Varner 1996), schools and universities (Cameron 1978;Zammuto and Krakower 1991;Berrio 2003;Kwam and Walker 2004); manufacturing companies (Zammuto and O'Connor 1992;Sousa-Poza et al 2001;Braunscheidel et al 2010); courier express delivery (Chan 1997); engineering and project management services (Igo and Skitmore 2006); civil engineering division of a Ministry (Schepers and Berg 2007); and public utility/administration organizations (Quinn and Spreitzer 1991;Talbot 2008). …”
Section: Application Domain: Organizational Culture and Valuesmentioning
confidence: 99%